Synthesis of Functionalized Heterocyclic Compounds Driven by Visible-Light Photocatalysis - Bouchet, Lydia María (2021)
The employment of visible-light has emerged as a powerful, selective, and sustainable tool for the construction and functionalization of heterocyclic systems. This review highlights the recent progress in protocols to obtain benzothiazoles, triazoles, and selenoindoles mediated by light providing overviews of their synthetic scope. In addition, the mechanisms involved are discussed.